(3eLed GdCSeGAs
(3ChdgG (B:s
(3ef Ohf MeOg hdGjHdZ hUa cfg bOQg heLOg GdcJGH GdeLed GdbSe GdChd ai GdMjhGfGJ heGjfGSHgG , hGdKGfi ai GdYdhjGJ s
(3BNQgG (B:s
(3hUfaJ JQLeJg eG GSJWYJ Yf hUeI GdHTGYI hGdSeGMI hHSWJ GdcdGe ajg Ydi UZQ MLeI hQLhf Cf jgJOi GdeJYde HVhA fLeI Je hced s
(3GdeNWhW HGddZJjf GdYQHjI hGdaGQSjgs
(3GdfSNI HgG MhGTs
(3HgG WeSs
(3ai MhGTjgG JYdjbGJ hTQhM s
(3eged GdfbW CMjGfG s
(3HgG fXGe GdJYbjHI s
Keywords: (3GddZIs